Residential Instability and Children’s Mental Health: Emotional and Behavioral Consequences of Frequent Relocation - C. J. Rodriguez-Perez; X. L. Castellanos (Studies in Social Science & Humanities, 2024)
Residential instability, characterized by frequent relocations, poses significant risks to children’s mental health, impacting their emotional and behavioral development. This study explores the emotional and behavioral consequences of frequent relocations on children aged 5 to 15, using a mixed-methods approach that combines longitudinal quantitative data and qualitative interviews. The findings reveal that children who experience three or more relocations within five years exhibit significantly higher levels of anxiety, depression, and attachment issues, alongside increased externalizing behaviors such as aggression and defiance and internalizing behaviors such as social withdrawal and anxiety. Academic performance also suffers, with lower average scores in core subjects like mathematics and reading observed among frequently relocated children. These outcomes are moderated by factors such as parental support, community integration, and economic stability, highlighting the complex interplay between individual, familial, and contextual variables. The study underscores the need for targeted interventions and supportive policies to mitigate the negative impacts of residential instability and promote children’s mental health and well-being. Future research should focus on the long-term effects, specific vulnerable populations, and protective factors to better understand and address the challenges faced by children in unstable housing situations.